Lower Limb Loading during Gait in Patients Long Period after Total Hip Arthroplasty Revision. (4th August 2016) - Kubonova, Eliska; Svoboda, Zdenek; Janura, Miroslav; Gallo, Jiri; Duskova, Sarka
Abstract : The aim of the study was to assess lower limb loading during walking after unilateral total hip arthroplasty (THA) revision. Twenty-three THA revision subjects (12 men, 11 women) were divided into three groups according to time since surgery as 1 to 6 years, 6 to 11 years, and over 11 years. Two force plates were used to measure the ground reaction force during the stance phase. On the operated limb, compared to nonoperated limb, we found lower first vertical peak in the group of 1 to 6 years after revision and lower propulsion peak in the group of 6 to 11 years since revision. In the group of 11 years since THA revision, no significant difference was found. With advancing years after surgery, the stance phase duration got reduced and propulsion peak increased in the operated limb; minimal vertical force decreased and the time of minimal vertical force increased in the nonoperated limb. The study findings suggest the tendency to a more gradual and safer weight acceptance on the operated limb during the first years after THA revision, followed by limitation of foot propulsion. Despite this fact, lower limb loading can be considered as symmetrical across the whole measured period.